(untitled) (Ameghiniana, 2025)
Nowadays, the polar desert of the Antarctic continent preserves a diverse Late Cretaceous terrestrial biota in the James Ross Basin. Within the upper section of the Santa Marta Formation (Santonian–middle Campanian; Chron C33n, 80 Ma), the Sitio Feliz locality preserves abundant permineralized plant remains in calcareous marine concretions. In this work, we provide the first taphonomic consideration of this concretionary material and illustrate the exceptional preservation of vegetative and reproductive plant organs in order to emphasize the quality of preservation of the new fossils that will permit full anatomical descriptions. Based on the presence of massive bioclast sediment, microframboids and framboids of pyrite, and fine microcrystalline calcite cement without dissolution or recrystallization evidence, we conclude that a rapid burial event and very early calcareous precipitation prevented bacterial decomposition in plant tissues and subsequent pyritization, as well as possible later bioturbation and compaction of the sediments. These conditions permitted the exceptional preservation of plant organs like the presence of delicate vascular and mesophyll cells, as well as various reproductive structures such as fruits and seeds with carpels and seed coats. Although concretionary levels within the Santa Marta Formation are common, the type of concretion described herein demonstrates a distinctive preservation, unlike other concretions described from the unit. The exceptional fossilization offers a rare opportunity to reconstruct the Antarctic continental floras in a much more complete approach than other types of paleobotanical remains.